USING METHODS OF SCIENTIFIC KNOWLEDGE FOR RESEARCH IN THE EDUCATION SPHERE - POLIAKOVA, Yuliia; NOVOSAD, Zoriana; ANILOVSKA, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to finding out the possibilities of using modern scientific methods of scientific knowledge, in particular the method of expert evaluations, when identifying trends in the development of the educational space in Ukraine and developing directions for its adaptation to internal conditions and global challenges. The characteristic features of the development of higher education in the conditions of globalization of the educational space are revealed. Emphasis is placed on actualizing the issues of using a complex of modern methods of scientific knowledge in the analysis of the processes taking place in the development of educational activity, for the adopting of well-founded decisions. The method of expert evaluations is recognized as one of these methods, the advantage of which is the possibility to make decisions when objective methods cannot give the desired result. The research was carried out on the example of the educational process of students of the first bachelor’s level in three educational and professional programs “Marketing”, “Advertising in Business” and “Law” of the Lviv University of Trade and Economics on the subject of determining the degree of conformity of forms, methods of learning and teaching to the principles of academic freedom and student-centered approach during training. A special questionnaire with a wide range of questions and proposed answers was used to implement the methodology, and a point scale was established for the possibility of processing the received data. To process the obtained assessment data, the widespread universal Microsoft Excel software package was used. As a result, it was established that the need to combine study and work, an excessive amount of study load and an inconvenient schedule are important for applicants. At the same time, the issues of insufficient provision of educational and methodical literature, lack of interest in education or employment prospects are of no importance. It is substantiated that the application of expert methods allows to carry out a quantitative assessment of the level of influence of factors on the education of students in educational and professional programs, and such an assessment can become the basis for further improvement of the educational process.
Keywords: higher education; globalization; educational and professional program; expert evaluation method; questionnaire